(untitled) (Journal of Scientific Research, 2016)
The present study was designed to confirm the traditional use of the fruits of Ficus hispida Linn. (Moraceae) as an antioxidant agent. Fruits of the plant extracted with methanol and crude methanol extract (CME) were further fractionated with n-hexane, chloroform, and ethyl acetate. All the fractions, n-hexane (NHF), chloroform (CHF), ethyl acetate (EAF), aqueous (AQF) and CME were preliminary screened for in vitro antioxidant activity and total phenolic and total flavonoid content. In DPPH radical scavenging assay, CME exhibited highest scavenging activity (IC50 = 11.20 µg/mL) as compared to other fractions. In this assay, IC50 of reference standard BHT was 5.10 µg/mL. The reducing power of the samples was in the order as AQF > CME > CHF > EAF > NHF. The results for hydrogen peroxide scavenging activity indicated that CME, EAF and AQF had almost the same scavenging activity except NHF. Total antioxidant capacity of CME and other fractions were ranked as CHF > AQF > CME > EAF > NHF. In the assay of antioxidant constituents (total phenol and total flavonoids content), the CME had highest phenolic and flavonoids content. The results indicate that Ficus hispida fruits could be considered as a potential source of natural antioxidant.